SISTEM ADMINISTRASI PENYALURAN GAS ELPIJI PADA PT. PURI KENCANA MERDEKA UTAMA (Fakultas Teknologi Informasi Universitas Stikubank (Unisbank) Semarang, 2013)
Administration system used by PT.Puri Kencana Merdeka Utama Semarang still using manual way and sometimes still make information delay for LPG full up. According to development information technology more fast, administration process can maximal with using information technology. This examine purpose are how to create computer administration system for PT.Puri Kencana Merdeka Utama Semarang. Computer administration system create by using Delphi and database My SQL programme. This conclude that the system create and implementation including user facility are administration, agent report, fleet agent report, fill up print, loading order print, prove print who can give ease in administration process. Keyword: Administration computer, Delphi, MySQL.